PANCHAYATI RAJ AND THE DEVELOPMENT OF SOCIAL INFRASTRUCTURE IN HANUMANGARH DISTRICT: AN ANALYTICAL STUDY - Divya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study evaluates the influence of Panchayati Raj Institutions (PRIs) on social infrastructure development, focusing on healthcare, education, and sanitation in Hanumangarh District, Rajasthan, from 2010 to 2020. Using secondary data, it examines PRIs’ effectiveness in enhancing rural life quality by improving infrastructure. The results show significant improvements in social infrastructure, attributed to the active role of PRIs in governance and project implementation. The paper provides detailed insights into PRIs’ achievements and challenges in decentralized rural governance, emphasizing their importance in advancing essential public services, which drive socio-economic progress in rural areas. This assessment aims to enhance understanding of decentralized governance mechanisms in rural India, highlighting both successes and challenges.